GmMYB176 Regulates Multiple Steps in Isoflavonoid Biosynthesis in Soybean - Anguraj Vadivel, Arun Kumaran; Renaud, Justin; Kagale, Sateesh; Dhaubhadel, Sangeeta (Frontiers in Plant Science, 2019)
Isoflavonoids are a group of plant natural compounds synthesized almost exclusively by legumes, and are abundant in soybean seeds and roots. They play important roles in plant-microbial interactions and the induction of nod gene expression in Rhizobia that form nitrogen-fixing nodules on soybean roots. Isoflavonoids also contribute to the positive health effects associated with soybean consumption by humans and animals. An R1 MYB transcription factor GmMYB176 regulates isoflavonoid biosynthesis by activating chalcone synthase (CHS)8 gene expression in soybean. Using a combination of transcriptomic and metabolomic analyses of GmMYB176-RNAi silenced (GmMYB176-Si), GmMYB176-overexpressed (GmMYB176-OE), and control soybean hairy roots, we identified a total of 33 differentially expressed genes (DEGs) and 995 differentially produced metabolite features (DPMF) in GmMYB176-Si hairy roots, and 5727 DEGs and 149 DPMFs in GmMYB176-OE hairy roots. By a targeted approach, 25 isoflavonoid biosynthetic genes and 6 metabolites were identified as differentially regulated in GmMYB176-OE and GmMYB176-Si soybean hairy roots. Taken together, our results demonstrate the complexity of isoflavonoid biosynthesis in soybean roots and suggest that a coordinated expression of pathway genes, substrate flux and product threshold level may contribute to the dynamic of the pathway regulation.